Frequency of Burnout Syndrome in an Intensive Care Unit of a Tertiary Care Hospital in Dhaka, Bangladesh (BIRDEM Medical Journal, 2019)
Background: Burnout syndrome is a psychological term resulting from prolonged exposure to job stressors. It is a very common problem among health professionals especially intensive care unit (ICU) staffs (physicians, nurses, ward-attendant), as ICUs are characterized by a high level of work related stress. The consequences associated with professional burnout affect both the healthcare professionals and recipients.Methods: This cross-sectional study was done over the period of four months (April to July, 2017) in the department of Critical Care Medicine, of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorder (BIRDEM) General Hospital, Dhaka. Total 93 ICU staffs were included as study population. After taking informed written consent, the participants were given a structured questionnaire consisting of 2 parts. Part 1 addressed demographic information including gender, age, credentials, employment status, years in practice, work schedule, hours worked per week, smoking and alcohol habit, involvement in teaching and research works. Part 2 of the handout was the Maslach Burnout Inventory - Human Service Survey (MBI-HSS); an inventory consisting of 22 questions to assess three components of burnout.Results: Among the 93 study participants 39.8% were physicians, 47.3% were nurses and 12.9% were wardattendants) were included in this study. Majority (52.7%) of the responders were found in the age group 20-29 year and 58.1% were married. Majority (58.1%) had a working experience of 1-5 year in ICU, where 61.3% staff had 20-25 working days/month. Regarding duty schedule, 84.9% staff were doing shifting duty, 83.9% had 6-10 working night shifts/month. Most (62.4%) were involved in 1-5 patients’ care during their duty time. Among all responders, 17.2% had habit of smoking and 4.3% had alcohol intake habit. 56.7% physicians were involved in research works, and 41.9% of total physicians and nurses were involved in teaching activities. Mostly (97.8% of all staff) followed the ICU guidelines. Regarding burnout scale, 50.5% of the staff had been suffering from moderate emotional exhaustion (EE), 46.2% of high EE. Majority (38.7%) had been suffering from low depersonalization (DP), 32.3% were in high DP and 29.0% were in moderate DP; 81.7% scored high on the personal accomplishment (PA) subscale.Conclusion: This study results suggest that majority of ICU staff are affected by some level of burnout syndrome.Birdem Med J 2019; 9(1): 30-34